2022
DOI: 10.3390/insects13050490
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Immune Induced Gene Expression Changes in Diverse Drosophila melanogaster Innate Immune Responses

Abstract: Organisms are commonly infected by a diverse array of pathogens and mount functionally distinct responses to each of these varied immune challenges. Host immune responses are characterized by the induction of gene expression, however, the extent to which expression changes are shared among responses to distinct pathogens is largely unknown. To examine this, we performed meta-analysis of gene expression data collected from Drosophila melanogaster following infection with a wide array of pathogens. We identified… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 150 publications
0
4
0
Order By: Relevance
“…We detected 10,903 transcripts, of which 379 (3.5%) were significantly increased in abundance in Gba1b mutants, while 175 (1.6%) were decreased in abundance. The transcripts most strikingly increased in abundance in Gba1b mutants included multiple members of the Turandot family, a group of genes transcribed in response to immune threats and stressors [27, 28], and the Tep (thioester-containing protein) family (Fig 1A), which is orthologous to the mammalian complement system [29, 30]. Enrichment analysis with PANGEA [31] revealed that the transcripts increased in abundance in Gba1b mutants were strongly enriched for immune- and defense-related functions (Fig 1B-C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We detected 10,903 transcripts, of which 379 (3.5%) were significantly increased in abundance in Gba1b mutants, while 175 (1.6%) were decreased in abundance. The transcripts most strikingly increased in abundance in Gba1b mutants included multiple members of the Turandot family, a group of genes transcribed in response to immune threats and stressors [27, 28], and the Tep (thioester-containing protein) family (Fig 1A), which is orthologous to the mammalian complement system [29, 30]. Enrichment analysis with PANGEA [31] revealed that the transcripts increased in abundance in Gba1b mutants were strongly enriched for immune- and defense-related functions (Fig 1B-C).…”
Section: Resultsmentioning
confidence: 99%
“…See Materials and Methods for full details. The example is based on the marker list from the immune meta-analysis study [28], which includes 55 transcripts. (A) Chance-level overlap (no enrichment).…”
Section: Supplementary Figure Legendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reasons might account for this. On the one hand, it is possible that there are significant differences in responses to infections with different pathogens, an aspect that is certainly important ( 38 , 39 ). On the other hand, these differences may also represent secondary effects that could be explained by different degrees of infection events and responses caused by them ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%